Participatory Laboratory Learning Approach in Pharmaceutical Analysis: Enhancing Skills and Professional Competence - Patil, Vrushali Vijay; Suryawanshi, Shailendra Sanjay (Innovare Journal of Education, 2026)
Participatory learning in laboratory-based pharmaceutical analysis has emerged as an effective educational approach for enhancing professional competence and practical skills in pharmacy students. Conventional laboratory instruction often restricts learning to demonstrations and predefined procedures, offering limited scope for independent reasoning, problem-solving, and analytical judgment. In contrast, recent curriculum reforms promote active and student-centered learning aligned with competency-based outcomes. Educational models such as problem-based learning (PBL), inquiry-driven chromatographic experiments, collaborative analytical method development, structured laboratory documentation, and peer-supported experimentation have shown measurable improvements in students’ technical proficiency, instrumental operation, regulatory awareness, and conceptual understanding. Furthermore, modern strategies, including virtual laboratory simulations, digital learning support systems, and the introduction of artificial intelligence–assisted tools, have increased accessibility while providing individualized learning experiences. These participatory environments encourage student engagement, responsibility, teamwork, and real-time decision-making skills that are highly valuable in research laboratories, quality control units, and professional analytical roles. Educators also benefit through improved student feedback, more meaningful assessments, and better monitoring of learning progression. Grounded in constructivist and experiential learning theories, participatory learning emphasizes knowledge building through hands-on experience and ongoing reflection. Overall, this approach strengthens analytical capabilities and helps bridge the gap between academic training and the evolving expectations of the pharmaceutical industry.